Exploring the impact of digital technology transformation in Islamic education: the Islamic education teachers perspective - Nor Alniza Azman; Mohd Isa Hamzah; Khadijah Abd Razak (Penerbit Universiti Kebangsaan Malaysia, 2024)
The empowerment of digital education is one of the government’s reforms to ensuring that Malaysia’s education system remains relevant. However, some teachers still do not recognise the significance of adopting digital technology, resulting in the rejection of a few Islamic education teachers. Thus, the purpose of this study is to investigate how Islamic education teachers perceive the impact of digital technology use in the classroom. Using a case study design and a qualitative research approach, the study included five Islamic education teachers who are proficient in digital technology and were chosen by a snowball sampling process. Interviews, in-person observations, and audio-visual analysis were used to gather data. Using NVIVO 14 software, the data was subjected to a thematic analysis. Credibility, transferability, and dependability are ensured for qualitative research data by triangulation, member check and peer review, rich and thick audit trail, and inter-rater. The study’s aims, which include improved productivity in the classroom; problem-solving efficacy; quick access to information; and more systematic data management, are addressed via four main themes and eight sub-themes. It is intended that this study will offer a viewpoint that encourages Islamic education teachers to make the most of digital technology in the classroom and in day-to-day operations.